Historical account of discoveries and travels in North America [electronic resource] : including the United States, Canada, the shores of the Polar Sea, and the voyages in search of a North-West Passage : with observations on emigration - Murray, Hugh, 1779-1846 (London : Longman, Rees, Orme, Brown, & Green; Edinburgh : Oliver & Boyd, 1829)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 38377-38379. "Vol. I." Electronic reproduction. Mode of access: Internet. 44